2008
DOI: 10.1007/s10157-007-0012-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum adiponectin and markers of endothelial injury in hemodialysis patients with arteriosclerosis obliterans

Abstract: A decrease in serum adiponectin levels and an increase in serum CD146 may be closely associated with the development of ASO, regardless of renal function. However, there are different mechanisms determining serum adiponectin levels in patients with normal kidney function and in hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…Although some studies [ 30 , 31 ] showed increased adiponectin level in patients with renal dysfunction but our study showed as the same of Shibata et al [ 32 ] that there is no association between adiponectin and renal function in atherosclerotic patients with normal renal function.…”
Section: Discussionsupporting
confidence: 53%
“…Although some studies [ 30 , 31 ] showed increased adiponectin level in patients with renal dysfunction but our study showed as the same of Shibata et al [ 32 ] that there is no association between adiponectin and renal function in atherosclerotic patients with normal renal function.…”
Section: Discussionsupporting
confidence: 53%
“…It has been shown that in hemodialysed patients, similarly to subjects with normal kidney function, lower plasma adiponectin concentrations are associated with cardiovascular complications: coronary artery disease or peripheral arterial occlusive disease (30,31). Similarly, plasma adiponectin concentration in peritoneal dialysis patients with carotid artery plaques was lower than in those without (32).…”
Section: Plasma Adiponectin Concentration and Vascular Pathology In Cmentioning
confidence: 99%
“…Adiponectin levels have been found to be decreased in obesity and increased during weight loss; however, CKD has been associated with markedly elevated levels of adiponectin probably due to its decreased renal excretion [13,14]. Previously, it has been demonstrated that adiponectin has potential antiinflammatory and anti-atherogenic properties due to its modulatory effect on endothelial adhesion molecules acting as protective factor against atherogenesis [15].…”
Section: Introducionmentioning
confidence: 99%